Inclusão escolar: um estudo acerca do atendimento ofertado ao aluno com transtorno do espectro autista do ensino fundamental I em Foz do Iguaçu no Brasil e em Puerto Iguazú na Argentina - Menezes, Luciene Acordi de (2024)
This dissertation consists of a study on the care of students with Autism Spectrum Disorder (ASD) in Elementary School I located in the context of school inclusion in the Brazilian (Foz do Iguaçu) and Argentina (Puerto Iguazú) Borders. Education recognizes the process of inclusive schooling of these students as a great challenge for all involved. The present research presents how students diagnosed with ASD are being cared for in a city in Brazil and one in Argentina, also presenting the main official documents of each country that guarantee school education to this public, as well as understanding inclusive education and the specificities of this disorder. We deal with the conceptions of development and learning from the perspective of the Historical-cultural Theory, which safeguards the importance of teacher mediation so that the learning and development of people with disabilities occurs. Authorization was obtained from the bodies responsible for education and special education in the two municipalities and approval from the Human Research Ethics Committee (CEP). We used the qualitative approach, carried out data collection with the bodies responsible for special education in each location, having started semi-structured interviews in August 2023, with those responsible for special education, with school principals and with teachers who work with students with ASD. The data obtained through the questionnaires were analyzed using the content analysis technique. This study provided a different view regarding the inclusion of students with ASD, as well as knowledge regarding this disorder that was not known before. If necessary, think again about initial and continuing education that really provides a differentiated view of inclusion, which seeks to build a truly inclusive society, which is not possible in an excluding society. It is therefore necessary to invest in public policies and continuous training, aiming for quality service and the permanence of all students in the inclusion process. This requires the implementation of concrete actions that address the diversity of educational needs, promote the constant training of education professionals, and ensure adequate pedagogical and technological resources. Only then will it be possible to build a truly inclusive school environment that respects individuality and ensures the full development of students in a context of equity and social justice.